Conflicts about urban green spaces in metropolitan areas under conditions of climate change: a multidisciplinary analysis of stakeholders’ perceptions of planning processes - Wagner, Madeleine; Mager, Christoph; Schmidt, Nicole; Kiese, Nina; Growe, Anna (Urban science, 2019)
Under conditions of climate change, land-use conflicts are a significant challenge for spatial planning, especially in densely populated metropolitan regions. By using a multi-methodological approach, this study aims to identify different stakeholders’ perceptions of these spaces in planning processes within urban areas in Germany. We use an ecosystem service analysis to evaluate the ecological potential of each selected study area and conducted a household survey to gauge how the local population and administration perceive them. The perceptions of these two groups of stakeholders regarding each area’s spatial qualities often differed from their actual ecological potential. We conducted interviews to identify possible conflicts between politicians and administration staff. While cooperation between politicians and the administration staff takes place and works well, the stakeholders involved often evaluate and perceive the cooperation processes in planning differently. Therefore, the authors argue that an integrative and methodologically multi-layered approach is useful for understanding complex perceptions in spatial planning.
Gesehen am 26.06.2020